2015
DOI: 10.11604/pamj.2015.20.384.6432
|View full text |Cite
|
Sign up to set email alerts
|

A spontaneous transomental hernia through the greater omentum

Abstract: Transomental hernia is the rarest form of internal hernias. Clinical expression of this pathology is ambiguous and diagnosis is often made at complication phase, after irreversible strangulation of the herniated loop. Radiological diagnosis is still difficult and intraoperative exploration usually allows discovering this pathology when patient is operated for acute intestinal obstruction. Treatment is surgical and aims to treat intestinal obstruction and prevent recurrence. We describe the case of a 65 years o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…Therefore, for the treatment of TOH, emergency surgery must be attempted as soon as possible. However, the preoperative diagnosis of TOH is difficult because clinical manifestations are nonspecific, as compared with other causes or types of strangulated SBO [3][4][5][6]11]. As a result, precise diagnosis in most TOH cases, as in our case, is made during emergency surgery for strangulated SBO [3][4][5][6].…”
Section: Discussionmentioning
confidence: 87%
See 4 more Smart Citations
“…Therefore, for the treatment of TOH, emergency surgery must be attempted as soon as possible. However, the preoperative diagnosis of TOH is difficult because clinical manifestations are nonspecific, as compared with other causes or types of strangulated SBO [3][4][5][6]11]. As a result, precise diagnosis in most TOH cases, as in our case, is made during emergency surgery for strangulated SBO [3][4][5][6].…”
Section: Discussionmentioning
confidence: 87%
“…However, the preoperative diagnosis of TOH is difficult because clinical manifestations are nonspecific, as compared with other causes or types of strangulated SBO [3][4][5][6]11]. As a result, precise diagnosis in most TOH cases, as in our case, is made during emergency surgery for strangulated SBO [3][4][5][6]. Recently, several studies have reported the usefulness of CT, especially multi-detector row CT, for the preoperative diagnosis of TOH [2,9,[12][13][14].…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations